Performance-Based seismic design and evaluation of out-of-code structure on Nanjing Financial City. (February 2023) - Yang, Qin; Zhang, Yujian; Yu, Shaole; Zhang, Qilin; Chen, Xinxi
Abstract: The main scope of performance-based seismic design and evaluation study focuses more on the seismic performance of the simple structure or the regular structure, instead of out-of-code structure. The C1 tower in Nanjing Financial City is taken as an engineering case study. Many design indexes of the original design scheme of the structure exceed the requirements of the existing Chinese specifications, such as the height exceed the limits, the torsional irregularity, the partial floor slab discontinuity etc., which are summarized in detail in this paper. Then, several special structural design strategies are adopted to improve the overall seismic performance of this out-of-code structure. For example, multiple lines of seismic defences are set and the outrigger trusses are strengthened to solve the height overrun. For torsion irregularity, the influence of the bidirectional seismic torsion effect is considered in the calculation. Finally, according to the results of dynamic elastoplastic time history analysis under rare earthquakes, the seismic performances of the out-of-code structure are evaluated in detail. The analysis results show that the overall seismic performances of the structure are all within a reasonable range, and the seismic performance of the main components in the structure all meet the specification requirements.